Value of catecholamine levels in the differential diagnosis of vasovagal syncope and psychogenic pseudosyncope in children - Wang, Hua; Ma, Wandong; Jin, Mei; Li, Bo; Sun, Suzhen (Frontiers in Pediatrics, 2024)
Background and purpose: Vasovagal syncope (VVS) and psychogenic pseudosyncope (PPS) can be difficult to distinguish, given their similar clinical presentations. This study was conducted to explore the clinical value of catecholamine levels in the differential diagnosis of VVS and PPS in children. Methods: This retrospective case-control study was conducted with data from children with VVS and PPS who underwent head-up tilt tests (HUTTs) at the Children’s Hospital of Hebei Province between March 2021 and March 2023. The data collected were baseline clinical characteristics, HUTT results, serum catecholamine levels in the supine and upright positions, and 24-hour urinary catecholamine concentrations. These variables were compared between the VVS and PPS groups. Results: From 328 potentially eligible cases, 54 (16.46%) cases of VVS and 24 (7.32%) cases of PPS were included in the analysis. No significant difference in age, sex, body mass index, or syncope frequency was observed between the VVS and PPS groups. The main predisposing factors for syncope were body position changes in the VSS group (83.33%) and emotional changes in the PPS group (41.67%). The episode duration was significantly shorter in the VSS group than in the PPS group (4.01 ± 1.20 vs. 24.06 ± 5.56 min, p < 0.05). The recovery time was also shorter in the VVS group than in the PPS group (1.91 ± 0.85 vs. 8.62 ± 2.55 min, p < 0.05). Relative to patients with PPS, those with VVS had significantly higher serum epinephrine (EP) levels in the upright position (199.35 [102.88, 575.00] vs. 147.40 [103.55, 227.25], p < 0.05) and lower serum epinephrine levels in the supine position (72.70 [42.92, 122.85] vs. 114.50 [66.57, 227.50], p < 0.05). Conclusions: Serum EP levels have potential value in the differential diagnosis of VVS and PPS.